Keterwakilan Perempuan Pada Lembaga Penyelenggara Pemilu Sebagai Hak Asasi Manusia - Agus Nardi Nasution; Sheila Hamdah Hanum Ritonga (Fakultas Hukum Universitas Islam Indonesia, 2024)
Human rights are the birth rights of humans given by God. According to Artidjo Alkotsar in his book Human Rights are natural rights which are a gift from Allah SWT. Human rights are not a gift from any authority, government body, law or party for anything. Based on the background above, the problem is formulated as follows: (1) What are the Human Rights Problems experienced by Women's Representation as Election Organizers?, (2) What is the legal protection for Women's Representation as Election Organizers in Indonesia? This research uses normative research, namely reviewing and analyzing statutory regulations relating to law, legal principles, legal standards. The results of this research show that women's representation in organizing general elections has not reached 30% as stated in the regulations of Law no. 7 of 2017 concerning Elections, so it is necessary for the government and election organizing institutions to provide education and training access to women, and protection for female organizers.